2017
DOI: 10.3349/ymj.2017.58.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Costs Attributable to Overweight and Obesity in Working Asthma Patients in the United States

Abstract: PurposeTo estimate annual health care and productivity loss costs attributable to overweight or obesity in working asthmatic patients.Materials and MethodsThis study was conducted using the 2003–2013 Medical Expenditure Panel Survey (MEPS) in the United States. Patients aged 18 to 64 years with asthma were identified via self-reported diagnosis, a Clinical Classification Code of 128, or a ICD-9-CM code of 493.xx. All-cause health care costs were estimated using a generalized linear model with a log function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Another study estimated health care costs attributable to obesity and overweight in working patients with asthma to be $878 and $257 in 2015 USD, per person per year, from 2003-2013. 22 Our adjusted analysis of the asthma cohort found that patients with class III obesity were associated with 18.1% higher 1-year total complication-specific costs versus patients with normal weight (P < 0.0001).…”
Section: Discussionmentioning
confidence: 79%
“…Another study estimated health care costs attributable to obesity and overweight in working patients with asthma to be $878 and $257 in 2015 USD, per person per year, from 2003-2013. 22 Our adjusted analysis of the asthma cohort found that patients with class III obesity were associated with 18.1% higher 1-year total complication-specific costs versus patients with normal weight (P < 0.0001).…”
Section: Discussionmentioning
confidence: 79%
“…Obesity accompanies various comorbid diseases including hypertension, diabetes, cardiovascular disease, renal insufficiency, and even cancer, and it causes tremendous economic burden 29,30 . Empagliflozin and dulaglutide could improve metabolic abnormality, lead to weight loss, and contribute to treating other obesity-related comorbid diseases 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, we could not analyze the potential variables that affect the frequency of visits and prognosis due to the retrospective nature of this study. For instance, adherence to medication, the dose of the inhaler, socio-economic status, clinical characteristics, residential district, and weather may be influential factors [ 26 , 27 ]. In this retrospective study, which used claim data from a national medical insurance review system, the available variables were extremely restricted.…”
Section: Discussionmentioning
confidence: 99%